Business Intelligence Analytics [Guest Editor's Introduction] - Fisher, Danyel; Drucker, Steven; Czerwinski, Mary (IEEE Computer Graphics & Applications, 2014)
This is the introduction to the CG&A Special Issue on Business Intelligence.